The Role of Electroencephalography in Children with Acute Altered Mental Status of Unknown Etiology: A Prospective Study - Chiarello, Daniela; Perrone, Annalisa; Ricci, Emilia; Ferrera, Giulia; Duranti, Francesca; Bonetti, Silvia; Marchiani, Valentina; Fetta, Anna; Lanari, Marcello; Cordelli, Duccio Maria (Neuropediatrics, 2024)
Introduction Acute altered mental status (AAMS) is often a challenge for clinicians, since the underlying etiologies cannot always easily be inferred based on the patient's clinical presentation, medical history, or early examinations. The aim of this study is to evaluate the role of electroencephalogram (EEG) as a diagnostic tool in AAMS of unknown etiology in children.Materials and Methods We conducted a prospective study involving EEG assessments on children presenting with AAMS between May 2017 and October 2019. Inclusion criteria were age 1 month to 18 years and acute (<1 week) and persistent (>5 minutes) altered mental status. Patients with a known etiology of AAMS were excluded. A literature review was also performed.Results Twenty patients (median age: 7.7 years, range: 0.5–15.4) were enrolled. EEG contributed to the diagnosis in 14/20 cases, and was classified as diagnostic in 9/20 and informative in 5/20. Specifically, EEG was able to identify nonconvulsive status epilepticus (NCSE) in five children and psychogenic events in four. EEG proved to be a poorly informative diagnostic tool at AAMS onset in six children; however, in five of them, it proved useful during follow-up.Conclusions Limited data exist regarding the role of EEG in children with AAMS of unknown etiology. In our population, EEG proved to be valuable tool, and was especially useful in the prompt identification of NCSE and psychogenic events.
Keywords: acute altered mental status; electroencephalogram; unknown etiology; children; diagnostic assessment